Α-Glucosidase inhibitory activity and structural characterization of polysaccharide fraction from Rhynchosia minima root. (January 2017) - Jia, Xuejing; Hu, Jie; He, Muxue; Zhang, Qingwen; Li, Peng; Wan, Jianbo; He, Chengwei
Highlights: PRM3 shows excellent α-glucosidase inhibitory activity. The detailed structures of PRM3 was elucidated. The repeating unit of PRM3 contains six residues. PRM3 has triple helix stereo-configuration. Abstract: Rhynchosia minima root, a renowned traditional Chinese medicinal herb, has been shown to exhibit multiple therapeutic activities. In this study, the α-glucosidase inhibitory activity of R. minima root polysaccharide fractions (PRM1, PRM3 and PRM5) is evaluated. PRM3 displays an excellent inhibitory activity with an IC50 value of 8.85 mg/mL, which is similar to that of acarbose, a positive control compound that has been applied for the control of postprandial hyperglycemia. PRM3 is a homogeneous fraction with an average molecular weight of 97.3 kDa. The results of methylation analysis, periodate oxidation and nuclear magnetic resonance (NMR) spectra reveal that the repeating units of PRM3 are mainly composed of (1 → 3, 4)-α-Ara p, (1 → 4, 6)-β-Gal p, (1 → 2, 4)-β-Rha p, (1 → 3, 4)-β-Gal p A, T-α-Ara f and T-α-Gal p residues. Moreover, triple helix stereo-configuration has been proven to exist in PRM3. In summary, the strong α-glucosidase inhibitory activity and unique structural feature of PRM3 suggest that it could have a potential application in functional foods.